Factors Impacting Participatory Post-Disaster Relocation and Housing Reconstruction: The Case of Tsholotsho District, Zimbabwe - Nombulelo Kitsepile Ngulube; Hirokazu Tatano; Subhajyoti Samaddar (International Journal of Disaster Risk Science, 2024)
Abstract Relocation is not typically considered the best planning option for post-disaster reconstruction and rehabilitation, but it may be necessary if the site has suffered severe damage or is at imminent risk. There is a growing recognition that strong community participation is necessary in the post-disaster relocation decision-making process since relocation can have detrimental effects on a community’s livelihood, cultural system, and way of life, among others. However, the realization of this still needs to be improved. As of yet, few studies have examined a comprehensive account of meaningful community engagement in post-disaster relocation and reconstruction, particularly in developing countries. This study investigated what factors influenced local communities’ participation in post-disaster relocation and reconstruction works after the 2017 Cyclone Dineo flood disaster in the Tsholotsho District of Zimbabwe. Qualitative research methods such as face-to-face interviews, observations, and focus groups were used to collect qualitative data from a purposive sample of 25 community members and 6 stakeholders. This empirical investigation showed that despite the fact that the relocation project was conceived as a community-centered project, there was no meaningful community engagement, due to the absence of a participatory framework or planning guidelines for stakeholder engagement, as well as the lack of political willingness among government officials. The study concluded that the lack of community involvement led to local communities abandoning the reconstruction sites because relocation projects failed to accommodate the cultural beliefs, place attachments, and livelihood concerns of local communities. This study suggested that it is imperative to enhance the awareness of government officials and other stakeholders about the importance of community participation for the effective implementation of post-disaster relocation works. Meaningful community participation can also provide avenues for incorporating local needs and concerns, cultural beliefs, and alternative and sustainable livelihood restoration, which are essential for effective reconstruction after disasters. This research aimed to enrich the academic discourse by providing valuable insights into the intricacies of post-disaster recovery initiatives in the country.